Assessment of gelatin hydrolysates from threadfin bream (Nemipterus hexodon) skin as a cryoprotectant for denaturation prevention of threadfin bream natural actomyosin subjected to different freeze-thaw cycles. (November 2022) - Kuepethkaew, Sakonwat; Klomklao, Sappasith; Benjakul, Soottawat; Betti, Mirko; Simpson, Benjamin K.
Highlights: Gelatin hydrolysate was produced from threadfin bream skin. Gelatin hydrolysate was able to prevent protein denaturation of freeze-thawed NAM. Hydrolysate could protect lipid oxidation of freeze-thawed NAM. It could serve as the functional ingredient to maintain the seafood quality. Abstract: Gelatin hydrolysates prepared from threadfin bream skin (GH) using lizardfish stomach pepsin (GHLP) with different degrees of hydrolysis (DHs: 10–40%) were studied as a potential alternative to commercial cryoprotectant (sucrose/sorbitol blend; SuSo, 1:1) used in frozen surimi. The characteristics of threadfin bream natural actomyosin (NAM) containing 8% GHLP with different DHs or SuSo were compared to control NAM before and after freeze-thaw treatment. After 3 and 6 freeze-thaw cycles, all present cryoprotectants retarded the protein changes. Among all samples, the highest Ca 2+ -ATPase activity, total sulfhydryl and solubility with the coincidental lowest disulfide bond content were observed in NAM added with GHLP having 20% DH after repeated freeze-thawing. Also, GHLP could prevent lipid oxidation in NAM as shown by the lower TBARS value. When cryoprotective properties of GHLP with 20% DH and GH prepared by papain (GHP) (DHs: 10–40%) were compared, the cryoprotectant properties of GHLP were similar to that of GHP. However, GHP with 10% DH exhibited a higher protective effect on protein denaturation. Hence, both GHLP and GHP with suitable DH can be a new generation cryoprotectant with the lower sweetness in surimi products.